Effects of Tai Chi on working memory in older adults: evidence from combined fNIRS and ERP - Wang, Chen; Dai, Yuanfu; Yang, Yuan; Yuan, Xiaoxia; Zhang, Mengjie; Zeng, Jia; Zhong, Xiaoke; Meng, Jiao; Jiang, Changhao (Frontiers in Aging Neuroscience, 2023)
Objective The study aimed to investigate the effects of a 12-week Tai Chi exercise intervention on working memory in older adults using ERP-fNIRS. Method Fifty older adults were randomly assigned to either an experimental group receiving a 12-week Tai Chi exercise intervention or a control group receiving regular daily activities. Working memory was assessed using the n-back task before and after the intervention, and spatial and temporal components of neural function underlying the n-back task were measured using ERP-fNIRS. Results The experimental group demonstrated significant improvements in reaction time and accuracy on the 2-back task and showed higher activation levels in the R-DLPFC. Additionally, the Tai Chi group displayed significant increases in P3 amplitude in the overall n-back task. Conclusion These findings suggest that Tai Chi interventions can enhance working memory in older adults, as evidenced by increasing neural activity and improving HbO in the R-DLPFC during the 2-back task.